2018
DOI: 10.1186/s12936-018-2486-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to improve malaria surveillance system preventing transfusion-transmitted malaria in blood banks using molecular diagnostic

Abstract: BackgroundMalaria can be transmitted by blood transfusion through donations collected from asymptomatic or parasitic donors. The parasites are released into the bloodstream during its life cycle and will therefore be present in donated blood by infected individuals. All cases of transfusion-transmitted malaria (TTM) notified since 2005 in Brazil were fatal. A good screening tool for Plasmodium spp. detection in blood units must have a high detection threshold, and the prevention of TTM relies entirely on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
13
0
4
Order By: Relevance
“…The Brazilian Amazon has large cities with millions of malaria-naïve individuals susceptible to infection. In these regions, a better tool for diagnosing malaria is needed and it is currently challenging to find a technique for screening blood donors that is easy to perform and can screen a large number of samples with high sensitivity [19]. PCR has been shown to be an effective tool for diagnosing human malaria parasites, even in mixed infections, and has proven to be a superior method to microscopy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Amazon has large cities with millions of malaria-naïve individuals susceptible to infection. In these regions, a better tool for diagnosing malaria is needed and it is currently challenging to find a technique for screening blood donors that is easy to perform and can screen a large number of samples with high sensitivity [19]. PCR has been shown to be an effective tool for diagnosing human malaria parasites, even in mixed infections, and has proven to be a superior method to microscopy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported the usefulness of mtDNA qPCR for the detection of P. vivax, P. falciparum and P. malariae , carried out in three different reactions. In a study conducted in the Brazilian Amazon region, 10 of 2,224 donor candidates were positive for P. vivax (0.45%) 16 . Our results detected two cases of P. malariae in 292 donor candidates tested (0.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Die PCR wurde hier als effektive Screeningmethode bei Blutspendern in einem Hochrisikogebiet für Malariaerreger eingeschätzt. Durch die PCR-Technik konnten verschiedene Plasmodienerreger, auch in sehr geringer Anzahl, schnell in Blutproben asymptomatischer Spender nachgewiesen werden [21]. Insbesondere der Nachweis von sehr geringen Erregermengen im Blut asymptomatischer Spender, bei denen eine subklinische Malariainfektion vorliegt, ist für die aktuellen Berichte der durch Transfusion übertragenen Malariafälle ausschlaggebend [22].…”
Section: Introductionunclassified